Parámetros de bienestar animal de los ovinos faenados en el camal municipal del cantón Guamote - Arellano Yasaca, Jorge Enrique (2022)
The research was carried out in the municipal slaughterhouse of the Guamote canton, with the objective of evaluating the animal welfare parameters of slaughtered sheep. This study is of a descriptive, observational, non-experimental cross-sectional type, for which data from 32 observations of sheep designated to the meat industry were collected in a period from May 2 to August 3, 2022. The observations were described by means of five rating criteria: bad, fair, good, very good and excellent, for which a rating scale of one to five points was used in accordance with the Welfare Qualite protocol, one being the rating for poor management and 5 for excellent handling. The results obtained show that in 60% of observed sheep the transport variable is qualified as "Regular", due to the poor conditions of the vehicles used for this purpose. In addition, the animals were handled in heterogeneous groups, which affects their behavior and health.